NILAI-NILAI DALAM PENDIDIKAN ISLAM MENUJU PARADIGMA PEMBELAJARAN QUR'ANI - Ahkmad Muadin (Nurul Jadid University, 2017)
Islam is the Shari'ah of Allah for mankind, in order that man performs worship to Him. In order for human beings to bear and realize the great mandate, the Shari'a requires practice, development, and coaching. Development and coaching that is what is meant by Islamic education. Understanding Education by Islam is the whole sense contained in terms ta'lim, tarbiyah, and ta'dib. Implementation of religious values in national education includes: the existence of religious subjects, institutes of religious education, attachment of religious values in every subject and the planting of religious values in the family. The basic purpose of learning is simplified into three, namely: retention goals, understanding goals and active goals. Values in Islamic education include ethical values, aesthetic values, exemplary and social values, values associated with individuals, values associated with the family, values relating to the life of the state and the values associated with religious.